Control of cell proliferation via elevated NEDD8 conjugation in oral squamous cell carcinoma - Kongthawat Chairatvit (2018)
A prominent feature of all cancers including oral carcinoma is an abnormality in cellular proliferation. Neural precursor cell-expressed developmentally down-regulated 8 (NEDD8) is a ubiquitin-like protein exerting its biological function through covalent ligation to a family of cullin proteins, which act as a component of the Skp1, cullin, and F-box protein complex that plays a critical role in the regulation of cell cycle. Using Western blot analysis, an increase in NEDD8 conjugation was observed in all highly proliferative cells, including immortalized normal oral keratinocyte (NOK), oral-derived carcinoma (KB, HSC4), and several types of human carcinoma cell lines as compared to normal human gingival fibroblast. The level of NEDD8 conjugation was proportionally dependent on the concentration of serum in culture medium, which also affected proliferation status of oral squamous cell carcinoma. NEDD8 conjugation was required for proliferation of the carcinoma cell since the transfection of dominant negative Ubc12 (Ubc12C111S) could prolong the rate of proliferation. Taken together, up-regulation of the NEDD8 conjugation is an essential requirement for the enhancement of proliferation of oral carcinoma cells. © Springer Science+Business Media, LLC 2007.